Visibility Is Not Equivalent to Confidence in a Low Contrast Orientation Discrimination Task - Rausch, Manuel; Zehetleitner, Michael (Frontiers in Psychology, 2016)
In several visual tasks, participants report that they feel confident about discrimination responses at a level of stimulation at which they would report not seeing the stimulus. How general and reliable is this effect? We compared subjective reports of discrimination confidence and subjective reports of visibility in an orientation discrimination task with varying stimulus contrast. Participants applied more liberal criteria for subjective reports of discrimination confidence than for visibility. While reports of discrimination confidence were more efficient in predicting trial accuracy than reports of visibility, only reports of visibility but not confidence were associated with stimulus contrast in incorrect trials. It is argued that the distinction between discrimination confidence and visibility can be reconciled with both the partial awareness hypothesis and higher order thought theory. We suggest that consciousness research would benefit from differentiating between subjective reports of visibility and confidence.